2020
DOI: 10.1038/s41598-020-74601-z
|View full text |Cite
|
Sign up to set email alerts
|

Predictive limitations of spatial interaction models: a non-Gaussian analysis

Abstract: We present a method to compare spatial interaction models against data based on well known statistical measures that are appropriate for such models and data. We illustrate our approach using a widely used example: commuting data, specifically from the US Census 2000. We find that the radiation model performs significantly worse than an appropriately chosen simple gravity model. Various conclusions are made regarding the development and use of spatial interaction models, including: that spatial interaction mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Other works also seek to understand what are the best parameters to use to obtain the best predictions of human mobility with this model. For example, [80] concluded that appropriate choices of input data and fitted parameters improves the predictive power of spatial interaction models like GM.…”
Section: Models and Methodsmentioning
confidence: 99%
“…Other works also seek to understand what are the best parameters to use to obtain the best predictions of human mobility with this model. For example, [80] concluded that appropriate choices of input data and fitted parameters improves the predictive power of spatial interaction models like GM.…”
Section: Models and Methodsmentioning
confidence: 99%
“…Constraints can also be considered in gravity models, these can be at the origin, at the destination or at both [ 162 , 163 ]. Assessing the effectiveness of these models is ongoing research [ 164 ], in some cases the scale of the system plays an important role [ 165 ], while in some others, the results from the radiation and gravity models are in agreement when assessing interventions [ 166 ].…”
Section: Urban Mobilitymentioning
confidence: 99%
“…Literature regarding land changes has discussed distal flows can be regarded as urban land teleconnections that drive and respond to urbanization (Seto et al, 2012). The gravity model is the most common formula for quantifying spatial interactions (Yan and Zhou, 2018;Hilton et al, 2020). Specifically, it allows us to measure location-based relationships by integrating the distance decay functions with measures of the relative scale of geographical entities (Haynes and Fotheringham, 1985).…”
Section: Graph-based Flow Magnitude Calculationmentioning
confidence: 99%